Liquid–Liquid Diffusion‐Assisted Crystallization: A Fast and Versatile Approach Toward High Quality Mixed Quantum Dot‐Salt Crystals. (24th March 2015) - Adam, Marcus; Wang, Zhiyu; Dubavik, Aliaksei; Stachowski, Gordon M.; Meerbach, Christian; Soran‐Erdem, Zeliha; Rengers, Christin; Demir, Hilmi Volkan; Gaponik, Nikolai; Eychmüller, Alexander
<x xml:space="preserve">Abstract</x> Here, a new, fast, and versatile method for the incorporation of colloidal quantum dots (QDs) into ionic matrices enabled by liquid–liquid diffusion is demonstrated. QDs bear a huge potential for numerous applications thanks to their unique chemical and physical properties. However, stability and processability are essential for their successful use in these applications. Incorporating QDs into a tight and chemically robust ionic matrix is one possible approach to increase both their stability and processability. With the proposed liquid–liquid diffusion‐assisted crystallization (LLDC), substantially accelerated ionic crystallization of the QDs is shown, reducing the crystallization time needed by one order of magnitude. This fast process allows to incorporate even the less stable colloids including initially oil‐based ligand‐exchanged QDs into salt matrices. Furthermore, in a modified two‐step approach, the seed‐mediated LLDC provides the ability to incorporate oil‐based QDs directly into ionic matrices without a prior phase transfer. Finally, making use of their processability, a proof‐of‐concept white light emitting diode with LLDC‐based mixed QD‐salt films as an excellent color‐conversion layer is demonstrated. These findings suggest that the LLDC offers a robust, adaptable, and rapid technique for obtaining high quality QD‐salts.